Konfigurationen : zwischen Kunst und Medien - Schade, Sigrid; Tholen, Georg Christoph; Angerer, Marie-Luise; Bahr, Hans-Dieter; Block, Friedrich W.; Burgin, Victor; Dröge, Franz; Ecker, Gisela; Ernst, Wolfgang; Fabo, Sabine; Frenkel, Vera; Gendolla, Peter; et al. (München : Wilhelm Fink Verlag München, 1999)
Angerer, Marie-Luise ; Antonioni, Michelangelo ; Avery, Tex ; Baraduc, Hyppolyte ; Beuys, Joseph ; Bódy, Gabor ; Bosch, Hieronymus ; Bronzino, Agnolo ; Dürer, Albrecht ; Export, Valie ; Fleischer, Alain ; Ford, John ; Frenkel, Vera ; Grandville, Ignac Isidore Gérard ; Grillenberger, Christian ; Huston, John ; Jung, Barbara ; Kandinsky, Wassily ; Leadbeater, Charles W. ; Mansell, Alice ; Meads, Mickey ; Murnau, Friedrich Wilhelm ; Van Ostade, Adriaen ; Preusser, Ludwig ; Renoir, Jean ; Schmelzdahin (Gruppe) ; Shaw, Jeffrey ; Sternberg, Josef von ; Syliboy, Alan ; Szyhalski, Piotr ; Tansey, Mark ; Thomadaki, Katerina ; Tillmans, Wolfgang ; Velázquez, Diego
Speciale kast : CD-Rom
Biog., bibliog. auteurs p. 523-535
Duits
boek